Analisis Tingkat Kemampuan Berpikir Kreatif Mahasiswa Calon Guru Matematika IKIP Mataram dalam Mengajukan Pertanyaan Matematika Efektif - Yuntawati Yuntawati (Jurnal Ilmiah Mandala Education (JIME), 2017)
The purpose of this research is to know the level of creative thinking ability of students of mathematics teacher candidate of IKIP Mataram in asking effective math question. The subject of this research is the students of semester V of Mathematics education program of IKIP Mataram, amounting to 30 students. The data collection technique is done by using the creative thinking ability test sheet. Data were analyzed based on indicators of creative thinking in asking effective mathematical questions that were associated with characteristics of creative thinking. The results showed that from 30 students who were subjects of research, 5 students were at level 4 which is the highest level in creative thinking level with very creative category, 6 students are in level 3 with creative category, 50 students are in level 2 with enough category creative. While level 1 and level 0 each there are 2 students with less creative and less creative category.